2019
DOI: 10.1371/journal.pone.0217873
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-household perceived relative inequality among disabled and non-disabled people in Liberia

Abstract: Evidence suggests that people with disabilities are the most marginalised and vulnerable group within any population. However, little is known about the extent of inequality between people with and without disabilities in contexts where the majority of persons experience extreme poverty and hardship. This includes in Liberia, where very little is understood about the lives of disabled people in general. This study uses a multidimensional wellbeing framework to understand perceived relative inequality associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These make it difficult to attribute transport-or lack of-as a singular cause for exclusion. In recent research undertaken by authors in Liberia [33], when asking matched household heads about barriers to accessing healthcare services, distance to health facilities was weighted similarly between disabled (11.0%) and non-disabled households (12.8%). Unfortunately, the study did not ask what the most commonly used mechanism of transport was, nor whether this resulted in additional costs, for example if persons with disabilities had to use more expensive means of transport (e.g., taxi cars instead of taxi motorbikes), or spend more on transport overall.…”
Section: Measuring Access To Servicesmentioning
confidence: 99%
“…These make it difficult to attribute transport-or lack of-as a singular cause for exclusion. In recent research undertaken by authors in Liberia [33], when asking matched household heads about barriers to accessing healthcare services, distance to health facilities was weighted similarly between disabled (11.0%) and non-disabled households (12.8%). Unfortunately, the study did not ask what the most commonly used mechanism of transport was, nor whether this resulted in additional costs, for example if persons with disabilities had to use more expensive means of transport (e.g., taxi cars instead of taxi motorbikes), or spend more on transport overall.…”
Section: Measuring Access To Servicesmentioning
confidence: 99%
“…This conceptualization of stigma as an interactional phenomenon “ based on multiple grounds, including prejudice, religious beliefs, low expectations and even fear ” was also outlined in the 2019 Report of the Office of the United Nations High Commissioner for Human Rights on Awareness-raising under article 8 of the Convention on the Rights of Persons with Disabilities [ 20 ], which recognizes the importance of understanding how disability stigma develops in order to design effective strategies to combat prejudice and discrimination. Yet, despite the intrinsic dual nature of stigma as a social and interactional construct, most empirical research carried out in this area aims at either evaluating the impact of stigma on people with disabilities [ 21 , 22 , 23 ] or developing and testing stigma-reduction strategies among people without disabilities [ 10 , 24 , 25 , 26 , 27 ]. Even when researchers have focused on identifying the main factors that shape stereotypes and stigma surrounding disabilities, this is usually from solely the perspective of people without disabilities [ 28 , 29 , 30 , 31 , 32 , 33 ] or, less commonly, looking at the construction of self-stigma among people with disabilities [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…This work is part of a larger study investigating multidimensional poverty at individual and household levels and the political and institutional conditions needed for poverty reduction for people with disabilities in Liberia [ 8 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The original research did not set out to focus on Ebola, but the outbreak began during the initial phase of the project, affording the unique opportunity for research on the consequences and impacts of the outbreak on people with disabilities in comparison to their non-disabled counterparts. In response, a set of Ebola-related questions was added to a household survey tool [ 8 ]. Research on other infectious diseases (in particular HIV/AIDS) has demonstrated how persons with disabilities are at significant disadvantage compared to their non-disabled counterparts for a range of reasons, including multidimensional poverty, gender, risk of sexual violence and limited social networks [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation